2002
DOI: 10.1002/med.10009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of phospholipid distribution across bilayer membranes

Abstract: Most biological membranes possess an asymmetric transbilayer distribution of phospholipids. Endogenous enzymes expend energy to maintain the arrangement by promoting the rate of phospholipid translocation, or flip-flop. Researchers have discovered ways to modify this distribution through the use of chemicals. This review presents a critical analysis of the phospholipid asymmetry data in the literature followed by a brief overview of the maintenance and physiological consequences of phospholipid asymmetry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
172
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(180 citation statements)
references
References 237 publications
0
172
2
5
Order By: Relevance
“…Alternatively, a more direct role of SLs in protecting Gap1 against ubiquitination could also be considered. Although mammalian SLs are known to reside mainly in the exoplasmic leaflet of the plasma membrane (Holthuis et al, 2001), ϳ20% of them are found in the cytoplasmic leaflet (Boon and Smith, 2002). Even if no data are currently available about the distribution of SLs over the two leaflets of the yeast plasma membrane (van Meer and Holthuis, 2000), it is thus conceivable that at least a small fraction of these lipids face the cytoplasm, in particular if they are forming a shell around transmembrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a more direct role of SLs in protecting Gap1 against ubiquitination could also be considered. Although mammalian SLs are known to reside mainly in the exoplasmic leaflet of the plasma membrane (Holthuis et al, 2001), ϳ20% of them are found in the cytoplasmic leaflet (Boon and Smith, 2002). Even if no data are currently available about the distribution of SLs over the two leaflets of the yeast plasma membrane (van Meer and Holthuis, 2000), it is thus conceivable that at least a small fraction of these lipids face the cytoplasm, in particular if they are forming a shell around transmembrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric lipid distributions between the inner and outer bilayer leaflets (35)(36)(37) were further considered to specifically model the composition of the inner leaflet of the plasma membrane (Table 1). To simulate the composition of a lipid raft (38 -41), we mixed sphingomyelin and cholesterol with zwitterionic PE and anionic PS ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Yet the understanding of the molecular mechanisms of lipid flip-flops is of substantial biological importance since a loss of transmembrane lipid asymmetry can have severe consequences. 10 For instance, while negatively charged phosphatidylserine lipids are usually located in the inner leaflet of the plasma membrane, their appearance in the outer leaflet is known to correlate with programmed cell death. 5 In more general terms, understanding how membrane lipids maintain the asymmetric transmembrane distribution and achieve their nonrandom distribution in cells is one of the key challenges in cell biology.…”
Section: Introductionmentioning
confidence: 99%